MiR‐21 antagonism reprograms macrophage metabolism and abrogates chronic allograft vasculopathy. Issue 10 (3rd May 2021) - Usuelli, Vera; Ben Nasr, Moufida; D'Addio, Francesca; Liu, Kaifeng; Vergani, Andrea; El Essawy, Basset; Yang, Jun; Assi, Emma; Uehara, Mayuko; Rossi, Chiara; Solini, Anna; Capobianco, Annalisa; et al.
Abstract : Despite much progress in improving graft outcome during cardiac transplantation, chronic allograft vasculopathy (CAV) remains an impediment to long‐term graft survival. MicroRNAs (miRNAs) emerged as regulators of the immune response. Here, we aimed to examine the miRNA network involved in CAV. miRNA profiling of heart samples obtained from a murine model of CAV and from cardiac‐transplanted patients with CAV demonstrated that miR‐21 was most significantly expressed and was primarily localized to macrophages. Interestingly, macrophage depletion with clodronate did not significantly prolong allograft survival in mice, while conditional deletion of miR‐21 in macrophages or the use of a specific miR‐21 antagomir resulted in indefinite cardiac allograft survival and abrogated CAV. The immunophenotype, secretome, ability to phagocytose, migration, and antigen presentation of macrophages were unaffected by miR‐21 targeting, while macrophage metabolism was reprogrammed, with a shift toward oxidative phosphorylation in naïve macrophages and with an inhibition of glycolysis in pro‐inflammatory macrophages. The aforementioned effects resulted in an increase in M2‐like macrophages, which could be reverted by the addition of L‐arginine. RNA‐seq analysis confirmed alterations in arginase‐associated pathways associated with miR‐21 antagonism. In conclusion, miR‐21 is overexpressed in murine and human CAV, and its targeting delays CAV onset by reprogramming macrophages metabolism. Abstract : The authors show that, after heart transplantation, microRNA‐21 is overexpressed in chronic allograft vasculopathy (CAV), that pharmacological and genetic modulation of microRNA‐21 mitigated CAV, and that microRNA‐21 antagonism abrogated CAV by reprogramming macrophage metabolism.